The Fed's TRAP: A Taylor-type Rule with Asset Prices - Alexander Erler; Christian Drescher; Damir Krizanac (Verein für Socialpolitik, 2010)
This paper examines if US monetary policy responds to asset prices. Using real-time data we estimate a Taylor-type rule with an asset price variable. This variable refers to real estate prices, considering that those exhibit an important share in households' asset portfolio. Moreover, especially real estate prices seem to have a close connection to monetary conditions. To analyze this link we describe price movements in the real estate price index by using a specific cycle dating procedure. The resulting variable indicates quasi real time bull and bear markets, and helps to evaluate the link between real estate market cycles and monetary policy. Our full-sample estimation results give reason to suppose that the US monetary policy responds in a pro-cyclical way to real estate prices. This result is supported by our rolling sub-sample estimations. Additionally, these also point to decelerating countermeasures of the Fed previous to asset price peaks.
Keywords: E52; E58; E50; 330; Fed; Monetary policy; Taylor rule; Asset Price Cycles; Real Estate